Translanguaging: Claudio Giovannesi's postcolonial practices. Issue 2 (2nd July 2016) - Duncan, Derek
Abstract: Claudio Giovannesi's Fratelli d'Italia (2009) is a documentary about the lives of three teenagers of non-Italian origins living in the Roman periphery. The third episode of the film features Nader, a second generation Italian–Egyptian and his conflicts both at school and in his family. Nader Sarhan starred in Giovannesi's later Alì ha gli occhi azzurri (2012), a feature film whose plot was loosely inspired by the life in Ostia of his younger self. Giovannesi blurs the line between documentary and fiction by casting Nader as 'himself' (members of his family also appear in both films). This blurring can be seen as one example of 'translanguaging', a way of moving across linguistic and cultural systems which suggests their permeability. Practices of translanguaging allow a movement across the familiar binary logic of the bi-national, pointing to quotidian practices of cultural difference with no clear culture of origin nor host. Nader's family's move between Arabic and Italian as they constantly re-negotiate their cultural values. Giovannesi reworks the familiar defining link between territory and language, yet the films offer no celebratory account of multilingual and multi-ethnic Europe.